On Price Adjustment Without an Auctioneer - Fisher, Franklin M. (Review of Economic Studies, 1972)
Journal Article On Price Adjustment without an Auctioneer Get access Franklin M. Fisher Franklin M. Fisher Massachusetts Institute of Technology and National Bureau of Economic Research Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 39, Issue 1, January 1972, Pages 1–15, https://doi.org/10.2307/2296439 Published: 01 January 1972